Effect of empagliflozin in hfref patients treated with angiotensin receptor neprilysin inhibitor an analysis of EMPIRE HF. (14th October 2021) - Omar, M; Hempel Larsen, J; Jensen, J; Kistorp, C; Videbaek, L; Kjaer Poulsen, M; Gustafsson, F; Koeber, L; Schou, M; Eifer Moeller, J; ,
Abstract: Introduction: Inhibition of neprilysin/valsartan (ARNi) or sodium glucose cotransporter 2 (SGLT2) in patients with heart failure (HF) and reduced ejection fraction (HFrEF) has been shown to reduce the risk of Cardiovascular death and hospitalization for HF. Recent trails suggested that SGLT2 reduces the risk for cardiovascular death or hospitalization for HF, regardless of underlying ARNi treatment and that the effect may even be greater in those receiving the combination. Whether there exist an interaction between effect of ARNi and SGLT2 on functional endpoints related to mechanism of action is unknown. Purpose: This post-hoc analysis of the randomized double-blinded Empire HF trial evaluated the influence of ARNi on the effect of the SGLT2 Empagliflozin on N-terminal prohormone B-type natriuretic peptide (NT-proBNP), pulmonary capillary wedge pressure (PCWP), Left ventricular end-systolic and end-diastolic volumes index; (LVESVI) (LVEDVI), left atrial volume index (LAVI), Left ventricular ejection fraction (LVEF), and Kansas City Cardiomyopathy Questionnaire (KCCQ) HFrEF patients. Methods: Empire HF trial randomized 190 patients with HFrEF (LVEF ≤40%) to placebo or empagliflozin (10 mg/day), on top of recommended treatment for HFrEF, for 12 weeks of treatment. A total of 58 (31%) received ARNi at baseline and no patients initiated ARNi during study period. Results: Patients on ARNi were well-treated with a similar baseline characteristic as those who were not treated with ARNi (Table 1). Patients with ARNi had a lower systolic blood pressure (P=0.01), with a higher NT-proBNP (P<0.001) when compared with those not receiving ARNi. When compared to placebo, empagliflozin did not reduce the ratio of change of NT-proBNP with or without ARNi (0.94 [95% CI, 0.75 to 1.19] pg/ml; P=0.62) and (1.02 [95% CI, 0.86 to 1.22] pg/ml; P=0.78), respectively, adjusted (age, atrial fibrillation) interaction P=0.57. Empagliflozin reduced PCWP regardless of ARNi treatment (with ARNi; −4.9 [95% CI, −9.1 to −0.6] mmHg; P=0.02) and (without ARNi; −2.1 [95% CI, −3.8 to −0.4] mmHg; P=0.01), adjusted interaction P=0.20. Overall, empagliflozin was associated with a reduction in LVESVI, LVEDVI, and LAVI volumes, but no effect on LVEF. However, Empagliflozin combined with ARNi at baseline, significantly reduced LVEDVI (−11.2 [95% CI, −21.2 to −1.2] ml/m 2 ; P=0.03), but not without ARNI (−2.9 [95% CI, −8.7 to 2.9] ml/m 2 ; P=0.32), adjusted interaction P=0.13. Treatment-by-subgroup interaction P-values for LVESVI, LAVI, and LVEF analysis were >0.05 (Figure 1). KCCQ total symptom score were significantly increased in those not receiving ARNi (5.4 [95% CI, 1.1 to 9.6]; P=0.013), but not with ARNi (−4.0 [95% CI, −10.3 to 2.3]; P=0.22), adjusted P=0.02. Conclusion: In this post hoc analysis the effects on empagliflozin to reduce PCWP and LV volumes were not diminished in patients receiving ARNi, however KCCQ change were diminished in patients receiving ARNi. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): This work was supported by the Danish Heart Foundation [grant numbers 17-R116-A7714-22076, 18-R124-A8573-22107]; Steno Diabetes Center Odense, Denmark [grant number 3363] and A.P. Møller Foundation for the Advancement of Medical Science [grant number 17-L-0339].